2022
DOI: 10.1111/imcb.12585
|View full text |Cite
|
Sign up to set email alerts
|

The effects of B‐cell–activating factor on the population size, maturation and function of murine natural killer cells

Abstract: The role of B‐cell–activating factor (BAFF) in B‐lymphocyte biology has been comprehensively studied, but its contributions to innate immunity remain unclear. Natural killer (NK) cells form the first line of defense against viruses and tumors, and have been shown to be defective in patients with systemic lupus erythematosus (SLE). The link between BAFF and NK cells in the development and progression of SLE remains unstudied. By assessing NK cell numbers in wild‐type (WT), BAFF−/− (BAFF deficient), BAFF‐R−/− (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The evidence of the effect of the BAFF-APRIL system on other immune cells is minimal. Pre-clinical work suggests that BAFF-BAFF-R signaling is critical for maintaining the splenic NK cell population at a steady state but is dispensable for NK cell maturation [ 94 ]. NK cells do not express BAFF receptors, neither at steady state nor in autoimmune conditions.…”
Section: Baff and April Signaling In Immune Homeostasismentioning
confidence: 99%
“…The evidence of the effect of the BAFF-APRIL system on other immune cells is minimal. Pre-clinical work suggests that BAFF-BAFF-R signaling is critical for maintaining the splenic NK cell population at a steady state but is dispensable for NK cell maturation [ 94 ]. NK cells do not express BAFF receptors, neither at steady state nor in autoimmune conditions.…”
Section: Baff and April Signaling In Immune Homeostasismentioning
confidence: 99%
“…In the salivary glands of pSS patients, subsets of unconventional NK cells that may produce inflammatory cytokines such as IL-22 were identified [ 59 ]. In addition, NK cells can facilitate BAFF production [ 60 ]. Furthermore, in pSS patients with EGMs, a higher number of NK cells was detected, implying their role in clinically aggressive disease [ 61 ].…”
Section: Pathogenic Mechanisms Of Pssmentioning
confidence: 99%
“…It was found that the expression levels of BAFF-R and TACI transcripts did not change signi cantly, but the transcription level of BCMA increased. When studying the relationship between BAFF and NK cells in the occurrence and progress of systemic lupus erythematosus, Quah PS et al found that BAFF signal is very important to maintain the number of NK cells in spleen through BAFF-R. BAFF has an indirect effect on NK cell homeostasis, but has no effect on NK cell function (Quah et al 2022). Rong HM team intend to explore the metabolic effects of BAFF-R on Pneumocystis pneumonia (PCP) (Rong et al 2023).…”
mentioning
confidence: 99%